Methicillin-Resistant Coagulase-Negative Staphylococci Carriage is a Protective Factor of Methicillin-Resistant Staphylococcus Aureus Nasal Colonization in HIV-Infected Patients: A Cross-Sectional Study - Ying Li; Jialing Lin; Linghua Li; Weiping Cai; Jiaping Ye; Suiping He; Wencui Zhang; Ning Liu; Zijun Gong; Xiaohua Ye; Zhenjiang Yao (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Methicillin-resistant coagulase-negative Staphylococci (MRCoNS) is regarded as the repository of mecA gene for methicillin-resistant Staphylococcus aureus (MRSA) and may develop methicillin-susceptible Staphylococcus aureus (MSSA) to MRSA. Therefore, we aimed to explore whether MRCoNS carriage is a risk factor of MRSA colonization. Phenotypic characteristics were performed to further assess the associations between MRSA and MRCoNS. Methods. This cross-sectional study was conducted in Guangzhou, China. Participants completed a questionnaire and provided a nasal swab for further analysis. The risk factors of MRSA colonization were analyzed using nonconditional logistic regression models. The phenotypic characteristics between MRSA and MRCoNS were compared by Chi-square test. Results. Among the 1001 HIV-infected patients, a total of 119 (11.89%) participants were positive for MRSA, and 34.45% (41/119) of all MRSA carriers were positive for MRCoNS. We found MRCoNS carriage was a protective factor of MRSA colonization (adjusted odds ratio = 0.59, 95% confidence interval: 0.38–0.91). A significant difference in the proportions of antibiotic resistance between MRSA and MRCoNS isolates was found except for penicillin, clindamycin, tetracycline, and teicoplanin. The main STs and CC types of MRSA isolates in this population were ST188 (15.1%) and CC59 (17.6%), respectively. Conclusions. HIV-infected patients remain a highly vulnerable population for MRSA colonization. Though who carried MRCoNS is less likely to have MRSA colonization, similarity of some antibiotic resistance between MRSA and MRCoNS was found in this study. Regular surveillance on the colonization and antibiotic patterns of MRSA and MRCoNS is still necessary.